2020
DOI: 10.3390/cancers13010061
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profile and Textural Characteristics of C595-Reactive MUC1 in Pancreatic Ductal Adenocarcinoma for Targeted Radionuclide Therapy

Abstract: Improvements in the prognosis of pancreatic ductal adenocarcinoma (PDAC) rely on the development of effective treatments to target advanced disease. Mucin 1 (MUC1) is a transmembrane glycoprotein which is involved in the metastatic progression of PDAC and is a receptor-of-interest for targeted radionuclide therapy. The aim of this study was to determine the feasibility of MUC1-based targeted radionuclide therapy for PDAC, by evaluating the expression profile of MUC1 in different pancreatic cells and tissues us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The utility of radioimmunotherapy can be improved by developing complementary imaging radioimmunoconjugates which allow for the informed selection of patients who have optimal expression of the target receptor for radioimmunotherapy [9,12]. We have previously identified MUC1-CE as an ideal target receptor given its expression is correlated with advanced PDAC and it is overexpressed on up to 90% of PDAC cells yet minimally expressed on normal cells [20][21][22]. Effective targeting of MUC1-CE is feasible using the C595 antibody and provides an avenue for radioimmunoconjugate development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The utility of radioimmunotherapy can be improved by developing complementary imaging radioimmunoconjugates which allow for the informed selection of patients who have optimal expression of the target receptor for radioimmunotherapy [9,12]. We have previously identified MUC1-CE as an ideal target receptor given its expression is correlated with advanced PDAC and it is overexpressed on up to 90% of PDAC cells yet minimally expressed on normal cells [20][21][22]. Effective targeting of MUC1-CE is feasible using the C595 antibody and provides an avenue for radioimmunoconjugate development.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the binding capacity of the radioimmunoconjugates to MUC1-CE, separate cell binding assays were performed using 177 Lu-DOTA-C595 and 64 Cu-DOTA-C595. Our previous work has identified that 93.1% of PANC-1 cells express MUC1-CE compared to only 11.5% of AsPC-1 cells (Supplementary Figure S2) [22]. Due to the variable MUC1-CE expression, these cell lines were used to evaluate for binding differences relative to MUC1-CE expression.…”
Section: Cell Binding Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucins are transmembrane glycoproteins highly expressed on several epithelial cancers, usually with an altered glycosylation pattern ( 37 , 298 ). MUC1 or cancer antigen 15-3 (CA 15-3) may have a role in the management of PDAC ( 299 ). Also, carbohydrate antigen 125 (CA125), an extracellular domain of MUC16, is a well-known ovarian cancer biomarker ( 38 ).…”
Section: Immunopet In Different Malignanciesmentioning
confidence: 99%